Spatial analysis of tuberculosis cases among stunted toddlers in Rambipuji District, Jember Regency - Utami, Wiwien Sugih; Amrina, Adinda Putri Yusri; Armiyanti, Yunita; Maududie, Achmad (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: The ongoing prevalence of tuberculosis (TB) and stunting presents significant health challenges, frequently localized within specific regions of Indonesia. Spatial analysis is essential in controlling infectious diseases like TB, as it identifies disease clusters and patterns of local TB spread within an area. Objective: This study aimed to analyze the distribution of TB cases among stunted children through spatial analysis. Methods: We used a cross-sectional analytical descriptive study. We interviewed parents of stunted children using a questionnaire. The diagnosis of TB was made based on the pediatric TB scoring table. Coordinate data of sample sites were obtained using a Geographic Information System (GIS), supported by risk factor analysis of TB. We then created a disease distribution map using the spatial analysis by Moran's Index and Nearest Neighbor Index (NNI) methods. Results: There were 15 childhood TB cases (8.2%) among stunted children in Rambipuji District. The spatial autocorrelation test using Moran's index showed that TB cases were clustered in Rambigundam village (Moran’s index 0.2364, p-value <0.05 and Z-score >1.96). The results of the NNI analysis showed dispersed results (p-value=0.000) in all villages. Conclusion: The distribution of childhood TB cases among stunted children in Rambipuji District is primarily random, except for Rambigundam Village, which shows a clustering of cases. According to the NNI methods, childhood TB cases among stunted children are spreading throughout all villages. These results underscore the need for initiatives to curb TB transmission, especially among stunted children, which should be targeted at all villages.